THE ATTITUDE TO THE EDUCATION OF WOMEN IN ISLAMIC PHILOSOPHY AND ITS GENDER ASPECTS (Scientific journal of the Fergana State University, 2023)
The article analyzes the matter of a Muslim person’s education in Islam religion and philosophy, its features, in particular, the influence of educated women on children upbringing and the rise of enlightenment of the society. The gender  features of this process are also enlightened..